Leisure of German Scholars in Russia in the Second Half of the 18th Century: Spaces of Adaptation - Rutsinskaya, Irina (Философия и культура, 2025)
This study is dedicated to the exploration of leisure practices of German scholars who worked in the Russian Empire in the second half of the 18th century. Invited to work at the St. Petersburg Academy of Sciences, they brought with them not only types and forms of scientific work but also a specific lifestyle and rituals of "scholarly leisure." Based on the analysis of letters and memoirs of well-known German scientists (such as G.F. Müller, P.S. Pallas, A.L. Schlötzer, and J. Steplin), as well as documents from their contemporaries, the main forms of leisure have been reconstructed and the spaces of their adaptation have been identified (private and public, social and symbolic). Particular attention is paid to intellectual leisure, which included practices that were previously uncommon in Russia. Collecting, correspondence, and building libraries became a way to transmit Enlightenment values and cultural habitus. The methodological approach combines cultural reconstruction of practices, historical-source analysis of everyday life, and philosophical reflection on leisure as a symbolic space structuring social identities. The scientific novelty of the work lies in rethinking the role of leisure as an active mediator of intercultural interaction and a crucial factor in the professional self-identification of the scientific community. The new profession of a scholar, which was institutionalized in the Russian Empire only in the 18th century, entailed the formation of specific models of behavior and self-presentation not only within the walls of the Academy but also in other sociocultural spaces. Through various private and public forms of leisure, there was an intensive transmission of not only relevant scientific knowledge but also fundamental norms of academic ethics, Enlightenment values, and models of social behavior of the intellectual elite. At the same time, these practices were not just transferred but transformed, reflecting the specifics of the Russian social and institutional context (the social circle and structure of leisure spaces changed, Russian forms of leisure were borrowed, and norms of court etiquette and patronage systems characteristic of the imperial environment were assimilated).